2013
DOI: 10.1016/j.nbd.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Preferential inactivation of Scn1a in parvalbumin interneurons increases seizure susceptibility

Abstract: Voltage-gated sodium channels (VGSCs) are essential for the generation and propagation of action potentials in electrically excitable cells. Dominant mutations in SCN1A, which encodes the Nav1.1 VGSC α-subunit, underlie several forms of epilepsy, including Dravet syndrome (DS) and genetic epilepsy with febrile seizures plus (GEFS+). Electrophysiological analyses of DS and GEFS+ mouse models have led to the hypothesis that SCN1A mutations reduce the excitability of inhibitory cortical and hippocampal interneuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 42 publications
9
131
1
Order By: Relevance
“…Selective deletion of Na v 1.1 channels in forebrain GABAergic interneurons fully reproduces the complex epilepsy and behavioural phenotypes of Dravet syndrome in these mice Ogiwara et al, 2013). Moreover, selective deletion of Na v 1.1 channels in excitatory neurons does not cause the disease traits of Dravet syndrome and can actually oppose the lethal effects of the disease by reducing the frequency of premature death (Dutton et al, 2012;Ogiwara et al, 2013). Thus, in mouse genetic models of Scn1a deletion, which reproduce all of the complex facets of Dravet syndrome, no evidence has emerged that alteration of excitability of pyramidal neurons contributes to causing disease phenotypes.…”
Section: Deletion Of Na V 11 In Pyramidal Neurons Does Not Cause Dramentioning
confidence: 85%
See 3 more Smart Citations
“…Selective deletion of Na v 1.1 channels in forebrain GABAergic interneurons fully reproduces the complex epilepsy and behavioural phenotypes of Dravet syndrome in these mice Ogiwara et al, 2013). Moreover, selective deletion of Na v 1.1 channels in excitatory neurons does not cause the disease traits of Dravet syndrome and can actually oppose the lethal effects of the disease by reducing the frequency of premature death (Dutton et al, 2012;Ogiwara et al, 2013). Thus, in mouse genetic models of Scn1a deletion, which reproduce all of the complex facets of Dravet syndrome, no evidence has emerged that alteration of excitability of pyramidal neurons contributes to causing disease phenotypes.…”
Section: Deletion Of Na V 11 In Pyramidal Neurons Does Not Cause Dramentioning
confidence: 85%
“…Loss-of-function mutations in Na v 1.1 cause Dravet syndrome in mice by selective impairment of excitability in GABAergic interneurons without detectable effects on excitatory neurons (Yu et al, 2006;Ogiwara et al, 2007;Cheah et al, 2012;Dutton et al, 2012;Tai et al, 2014). PV interneurons preferentially form synapses at the perisomatic region of their target cells, thereby controlling neuronal activity and spike output, whereas SST-expressing interneurons preferentially contact the distal dendrites, which allow them to efficiently control the impact of synaptic inputs near these sites (Klausberger and Somogyi, 2008;Harris and Mrsic-Flogel, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Kv3.2 knock-out mice show an increased susceptibility to epileptic seizures and disturbed cortical rhythmic activity [34] . In a study of the relative contribution of inhibitory interneurons and excitatory pyramidal cells to SCN1A-derived epilepsy, Dutton found that the inactivation of one Scn1a allele in PV interneurons reduces the seizure threshold, whereas the threshold is unaltered following its inactivation in excitatory cells [36] . These results demonstrated that specific ion channels of interneurons play a signifi cant role in epileptogenesis.…”
Section: Pv-immunoreactive (Pv-ir) Interneurons Arementioning
confidence: 99%